1983
DOI: 10.1007/bf00254259
|View full text |Cite
|
Sign up to set email alerts
|

Guanine ribonucleotide depletion in mammalian cells

Abstract: In a previous report we demonstrated in mouse lymphoma (S-49) cells that DNA synthesis inhibition resulting from guanine starvation is associated with GTP rather than dGTP depletion. Since several effective anticancer drugs act via guanine depletion, it is important to test whether critical GTP depletion is unique to S-49 cells or also occurs in other cell lines. Mycophenolic acid-induced guanine starvation caused a drastic DNA synthesis inhibition in the human lymphoblastic T leukemia (CEM) and the mouse B le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…In the present study, we showed that MPA and LE540, a RAR antagonist, activate only CMA, but not mA (Figs 5,7,S5 in Supporting Information). Because these compounds regulate LAMP2A, a lysosomal CMA receptor (Nguyen et al 1983;Bandyopadhyay et al 2010), our present finding is consistent with previous reports. Although two compounds that we examined in the present study do not affect mA activity, there would be some compounds that affect mA as well as CMA.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, we showed that MPA and LE540, a RAR antagonist, activate only CMA, but not mA (Figs 5,7,S5 in Supporting Information). Because these compounds regulate LAMP2A, a lysosomal CMA receptor (Nguyen et al 1983;Bandyopadhyay et al 2010), our present finding is consistent with previous reports. Although two compounds that we examined in the present study do not affect mA activity, there would be some compounds that affect mA as well as CMA.…”
Section: Discussionsupporting
confidence: 93%
“…Because RARa agonist is reported to increase the CMA activity by the up-regulation of LAMP2A (Anguiano et al 2013 antagonist, would increase CMA activity. MPA is reported to increase the CMA activity by decreasing GTP (Nguyen et al 1983) and stabilizing the CMA translocation complex at the lysosomal membrane (Bandyopadhyay et al 2010). In control siRNA-transfected cells, 5 lM MPA significantly increased GAPDH-HT puncta, and 10 lM LE540 tended to increase its puncta, but not significantly ( Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…3F, bottom). Depletion of intracellular levels of GTP with mycophenolic acid (MPA), a potent selective inhibitor of GTP synthesis shown to reduce intracellular levels of this nucleotide by up to 80% (Nguyen et al, 1983), led to a significant increase in rates of protein degradation (Fig. 3G).…”
Section: Resultsmentioning
confidence: 99%